The Cambridge paperback encyclopedia (New York, 1995)
This book has been fully revised, updated, supplemented and redesigned. Over 20000 entries and almost one million words ensure that is this one of the fullets and most comprehensive general reference books available in a concise form
Keywords: english language - encylopedias